Living High - Training Low: effect of 3 different patterns of exposure on acclimatization in elite athletes - Brugniaux, J. V.; Schmitt, L.; Robach, P.; Jeanvoine, H.; Zimmermann, H.; Nicolet, G.; Duvallet, A.; Fouillot, J.-P.; Richalet, J.-P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Exposure to chronic hypoxia is known to induce ventilatory acclimatization. This adaptation consists in a gradual and progressive time-dependent increase in ventilation (Powell and al, 2000). Another sign of acclimatization is an increase in arterial O2 content as a response to the hypoxic stimulus (Calbet and al, 2003). On arrival at altitude (above 2000m) people often suffer from Acute Mountain Sickness (AMS). Chronic exposure to altitude can also induce cardiac morphological changes due to pulmonary hypertension (Hultgren and al, 1965). While chronic exposure is well documented there is still interrogations about intermittent exposure, moreover for elite athletes. The aim of this study was 1) Evaluate the consequences of 3 different exposures to "living high - training low" method on clinical status and physiological markers of acclimatization, 2) Verify if these consequences persist 15 days after the end of training, 3) Assess whether these markers may predict the individual tolerance for this type exposure. METHODS: 41 athletes from 3 federations (11 cross-country skiers, 18 swimmers and 12 athletes) performed a 13-day (swimmers) or 18-day (swimmers, athletes) training period at 1100m, by sleeping either at 1100m (CON, n=5, 9, 6 respectively) or in hypoxic rooms (HYP, n=6, 9, 6 respectively), O2 fraction corresponding to 2500m (3 to 6 nights), 3000m (6 to 15 nights) and 3500m (6 nights for skiers). Measurements performed at 1100m before (PRE), 1 day (POST1) or 15 days (POST2) after training were cardiac function (echocardiography) and ventilatory response to hypoxic exercise (HVRe). Skiers realized these 2 tests at PRE and POST2 and the others at PRE and POST1. Lake Louise AMS score and arterial O2 saturation during sleep (SaO2, %) were measured daily for HYP. RESULTS: Subjects did not complain of headache, gastrointestinal or dizziness symptoms. Fatigue and sleep disturbances were frequently mentioned in both groups. Mean SaO2 decreased progressively (92.5 at 2500, 92 at 3000, 89.8 at 3500m for all subjects) with altitude but tended to increase with acclimatization. Cardiac function was not modified by this type of training: left ventricular dimensions and contractility, right ventricular dimensions, pulmonary arterial pressure did not change. Ventilatory response at exercise increased at the end of training. Hypoxia-induced desaturation at exercise decreased at the end of training (27.9 vs.21.5 for HYP). Signs of acclimatization had disappeared at POST2. HVRe was not a predictive factor but basal Red Cell Volume tended to be negatively correlated (n=38, p=0.08) with variations in . 2maxOV& DISCUSSION/CONCLUSIONS: This type of stage did not induce any significant clinical disorder. Cardiac morphological changes may occur, but all parameters stayed in the normal physiological range. SaO2 should be monitored to detect marked desaturation. A 10 to 15-day exposure to hypoxia at a maximal altitude of 3000m is sufficient to trigger ventilatory acclimatization, which fades away 15 days after training. Sato and al (1994) also showed this decrease in the ventilatory response to hypoxia 12 days after continuous exposure. HVRe, which is known to correlate with the quality of acclimatization, is not predictive of improvement in performance induced by "living high - training low" training.